What are the trends and demographics in sports-related pediatric spinal cord injuries?. Issue 1 (2nd January 2018) - Nadarajah, Vidushan; Jauregui, Julio J.; Perfetti, Dean; Shasti, Mark; Koh, Eugene Y.; Henn, Ralph Frank
ABSTRACT: Objectives : Pediatric spinal cord injury (PSCI) is a devastating injury that can cause significant long-term consequences. The purpose of this study is to calculate and report the prevalence of PSCI, identify risk factors for sports-related PSCI, and evaluate associated factors. Methods : The data sets of the Healthcare Cost and Utilization Project (HCUP) Kids' Inpatient Database (KID) from 2000–2012 were analyzed using ICD-9-CM external cause of injury codes to identify the mechanism of injury contributing to PSCI hospitalization. We then extracted demographic data on each admission including age, gender, race, and year of admission. We further stratified the data by sports-related cases of injury. Multivariate logistic regression analyses were used to identify independent risk factors. Results : Of our study population, 0.8% had a documented diagnosis of spinal cord injury (SCI). The most common documented external cause of injury code was motor vehicle accidents, representing roughly half of all cases in patients 0–9 years-old (p = 0.001). PSCI due to sports as an external cause of injury was more prevalent in patients 10–17 years old, and was especially prevalent in the 10–13 year-old age category in which sports-related PSCI reached a high of 25.6%. Risk factors for traumatic PSCI after a sports-related external cause included being of older age, male, and white. Conclusions : The prevalence of SCI increased with age. Given the popularity of youth sports in the United States, parents and sports officials should be aware of the increased risk of sports-related PSCI among patients 10–17 years old. Level of evidence : Level III, retrospective cohort study